Effect of edible coating on thermoplastic nylon denture base after soaking in distilled water and green tea on water absorption: Study observational - Rafly, Muhammad; Wahyuni, Siti (Padjadjaran Journal of Dental Researchers and Students, 2023)
ABSTRACTIntroduction: Thermoplastic nylon is public favorite denture base material because it has excellent aesthetic, low solubility and high flexibility but has drawback, high water absorption which can reduce the resistance of nylon used as denture base. Edible coating is natural polymer coating material and can be good alternative because of it’s barrier against external elements. This study aims to determine the effect of edible coating on thermoplastic nylon denture base after soaking in distilled water and green tea on water absorption. Methods: The research design was experimental laboratory with post-test only control group design. The research sample was cylindrical thermoplastic nylon with diameter 40 ± 1 mm and thickness 2 ± 1 mm based on ISO 20795-1 specifications. Water absorption was measured using the formula m2-m3/V (ISO/DIS 4049), analyzed by univariate test and Levene's test. Results: The mean value of water absorption in the sample group immersed in distilled water (A) 4.88 ± 0.34 g/mm3, with edible coating (B) 3.80 ± 0.37 g/ mm3, the sample group soaked in green tea (C) was 4.43 ± 0.18 g/mm3 and with edible coating (D) was 3.58 ± 0.39 g/mm3. Then the data were analyzed using One-way ANOVA test with p-value = 0.0001 (significancy at p <0.05). Conclusion: The results showed that there was significant effect of edible coating on thermoplastic nylon denture base after soaking in distilled water and green tea on water absorption. KEY WORDS: denture base, thermoplastic nylon, water absorption, edible coating, green teaPengaruh pelapisan edible coating pada basis gigi tiruan nilon termoplastik setelah direndam dalam akuades dan teh hijau terhadap penyerapan air: Studi eksperimentalABSTRAK Pendahuluan: Nilon termoplastik merupakan bahan dasar gigi tiruan yang banyak diminati oleh masyarakat karena memiliki nilai estetika yang baik, kelarutan rendah dan tinggi fleksibilitas namun memiliki kekurangan yaitu daya serap airnya yang tinggi. Penyerapan air tinggi akan mempengaruhi sifat dan struktur nilon sehingga menurunkan ketahanan nilon yang digunakan sebagai basis gigi tiruan. Edible coating merupakan bahan pelapis polimer alami dan dapat menjadi alternatif yang baik karena dapat berfungsi sebagai penahan terhadap unsur luar. Penelitian ini bertujuan untuk mengetahui pengaruh pelapisan edible coating pada basis gigi tiruan nilon termoplastik setelah direndam akuades dan teh hijau terhadap penyerapan air. Metode: Rancangan penelitian adalah eksperimental laboratoris post-test only control group design. Sampel penelitian nilon termoplastik berbentuk silindris dengan ukuran diameter 40 ± 1 mm dan ketebalan 2 ± 1 mm berdasarkan spesifikasi ISO 20795-1. Penyerapan air diukur menggunakan rumus m2-m3/V (ISO/DIS 4049). Nilai penyerapan air dianalisis dengan uji univariat dan uji levene. Hasil: Nilai rerata penyerapan air kelompok sampel yang direndam dalam akuades (A) adalah 4,88 ± 0,34 μg/mm3, dan dilapisi edible coating (B) adalah 3,80 ± 0,37 μg/mm3, kelompok sampel direndam dalam teh hijau (C) adalah 4,43 ± 0,18 μg/mm3 dan dilapisi edible coating (D) adalah 3,58 ± 0,39 μg/mm3. Lalu data dianalisis menggunakan uji One-way ANOVA dengan nilai p=0,0001 (signifikansi pada p<0,05). Simpulan: Hasil penelitian menunjukkan adanya pengaruh yang signifikan akibat pelapisan edible coating pada basis gigi tiruan nilon termoplastik setelah direndam dalam akuades dan teh hijau terhadap penyerapan airKATA KUNCI: basis gigi tiruan, nilon termoplastik, penyerapan air, edible coating, teh hijau